W gamma Production and Limits on Anomalous WW gamma Couplings in p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Sajot, G.; et al. (Amer Physical Soc, 2011)
We measure the cross section and the difference in rapidities between photons and charged leptons for inclusive W(-> l nu) + gamma production in e gamma and mu gamma final states. Using data corresponding to an integrated luminosity of 4.2 fb(-1) collected with the D0 detector at the Fermilab Tevatron Collider, the measured cross section times branching fraction for the process p (p) over bar -> W gamma + X -> l nu gamma + X and the distribution of the charge-signed photon-lepton rapidity difference are found to be in agreement with the standard model. These results provide the most stringent limits on anomalous WW gamma couplings for data from hadron colliders: -0.4 < Delta kappa(gamma) < 0.4 and -0.08 < lambda(gamma) < 0.07 at the 95% C.L.